A New Technical Approach for Cross-species Examination of Neuronal Wiring and Adult Neuron-glia Functions. (1st January 2023) - Edwards-Faret, Gabriela; de Vin, Filip; Slezak, Michal; Gollenbeck, Lennart; Karaman, Ruçhan; Shinmyo, Yohei; Batiuk, Mykhailo Y.; Pando, Carmen Menacho; Urschitz, Johann; Rincon, Melvin Y.; Moisyadi, Stefan; Schnütgen, Frank; et al.
Graphical abstract: Highlights: Single-plasmid approach with multiple expression modules (including self-excising piggyBac transposase). Allows simultaneous loss- (shRNA, CRISPR/Cas9) and gain-of-function (protein overexpression) experiments. Applicable across diverse (non-transgenic) species including mouse, rat, ferret and Xenopus tropicalis . Cell-type specific and temporal (CreER T2 ) control. Abstract: Advances in single cell sequencing have enabled the identification of a large number of genes, expressed in many different cell types, and across a variety of model organisms. In particular, the nervous system harbors an immense number of interacting cell types, which are poorly characterized. Future loss- and gain-of-function experiments will be essential in determining how novel genes play critical roles in diverse cellular, as well as evolutionarily adapted, contexts. However, functional analysis across species is often hampered by technical limitations, in non-genetic animal systems. Here, we describe a new single plasmid system, misPiggy. The system is based around the hyperactive piggyBac transposon system, which combines stable genomic integration of transgenes (for long-term expression) with large cargo capacity. Taking full advantage of these characteristics, we engineered novel expression modules into misPiggy that allow for cell-type specific loss- and gain-of-gene function. These modules work widely across species from frog to ferret. As a proof of principle, we present a loss-of-function analysis of the neuronal receptor Deleted in Colorectal Cancer (DCC) in retinal ganglion cells (RGCs) of Xenopus tropicalis tadpoles. Single axon tracings of mosaic knock-out cells reveal a specific cell-intrinsic requirement of DCC, specifically in axonal arborization within the frog tectum, rather than retina-to-brain axon guidance. Furthermore, we report additional technical advances that enable temporal control of knock-down or gain-of-function analysis. We applied this to visualize and manipulate labeled neurons, astrocytes and other glial cells in the central nervous system (CNS) of mouse, rat and ferret. We propose that misPiggy will be a valuable tool for rapid, flexible and cost-effective screening of gene function across a variety of animal models.